Water relations of chives in function of salinity and circulation frequency of nutrient solutions - Silva Júnior,Fernando J. da (2019)
ABSTRACT Hydroponic cultivation using saline waters is an alternative for agricultural production, especially in the cultivation of vegetables. Therefore, the present work was conducted with the objective of evaluating the water consumption, water use efficiency and water content, as well as dry matter partitioning of chives (Allium schoenoprasum), cv. Todo Ano Evergreen – Nebuka exposed to six levels of nutrient solution salinity (1.5, 3.0, 4.5, 6.0, 7.5 and 9.0 dS m-1), applied at two circulation frequencies (twice a day at 8 and 16 h; and three times a day - at 8, 12 and 16 h). The level in the nutrient solution reservoir, which decreased according to the water consumption by plants, was replaced with the respective saline water (Experiment I) and supply water (Experiment II). Both experiments used a completely randomized design, in a 6 x 2 factorial scheme, with five replicates. It was observed that increased circulation frequency and the use of supply water in the replacement mitigated the effects of salinity on water consumption, water use efficiency and water content in the plant. However, with the increase in nutrient solution electrical conductivity, dry matter allocation in the roots increased, to the detriment of the shoots.